FAKTOR-FAKTOR RISIKO RISIKO DALAM PERUSAHAAN JASA PENGIRIMAN - Resista Vikaliana (Institut Ilmu Sosial dan Manajemen Stiami, 2017)
In this era of globalization, can not be denied that the delivery of goods is needed, either by individuals or by organizations / companies. Delivery of goods (raw materials, semi-finished materials, or finished goods) that are not timely can cause inhibition of the production process. Package delivery service is a business services meripan goods that are very much the competition, therefore the income of goods services companies especially package goods packages tend to fluctuate decline as experienced by one of the domestic delivery services. With so many business competition for goods merchandise services, competition in the future will increase or change faster so that the demand map of these services will also change, if the service company does not follow the change impossible the company will exist. That is why management is required for the risks that often arise in the delivery of goods. Risk management steps that can be done include the management of human resources business competition freight services, delivery errors, goods damage sent, theft or fire warehouse. By knowing the various risks typically faced by the company, then handling the risks quickly and accurately can minimize the risks faced by the company, so spend large funds.